Arrhythmia-induced cardiomyopathy: unveiled after electrical cardioversion. (2nd May 2022) - Menezes Fernandes, R; Mota, T; Costa, H; Espirito Santo, M; Bento, D; Candeias, R; Mimoso, J; Jesus, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Arrhythmia-induced cardiomyopathy (AIC) is an important cause of left ventricular (LV) dysfunction, confirmed by the reversal of cardiomyopathy after controlling the arrhythmia. It requires a high index of suspicion. Purpose: To determine the prevalence and prognosis of AIC in patients referred to electrical cardioversion (EC) due to atrial fibrillation (AF) or atrial flutter (AFL). Methods: We conducted a retrospective study encompassing patients referred to EC due to AF/AFL in our Cardiology Department, from September 2011 to September 2020. Clinical characteristics, echocardiographic studies and follow-up data were analysed. Reduced LV ejection fraction (LVEF) was defined as LVEF lower than 50%. Primary endpoints were all-cause mortality and cardiovascular (CV) death. We excluded patients with no information regarding LVEF before and after the EC. Results: A total of 719 patients were referred to EC during the 9-year period, with a median age of 67 years-old and 70, 4% male predominance. EC was successfully performed in 93, 2%. Regarding patients with available LVEF data, only 123 patients (28, 9%) had reduced LVEF before EC. Of these, 24, 4% of patients were diagnosed with AFL, 59, 3% had arterial hypertension, 26, 9% were obese, 24, 4% had ischemic heart disease and 7, 3% had sleep apnea. Persistent AF/AFL was identified in 60, 3%, 23, 1% presented with first diagnosed AF/AFL and 15, 7% had paroxysmal episodes. 57 patients (46, 3%) had documented reversal of LV dysfunction after EC (improvement of a median LVEF of 41% to 59% after EC), confirming AIC diagnosis. Comparing to patients who did not recover LV function after EC, AIC patients had a larger prevalence of persistent AF/AFL (75% vs 45, 2%; p=0, 01), were more frequently cardioverted in an outpatient setting (68, 4% vs 46%; p=0, 047) and had lower prevalence of ischemic heart disease (5, 3% vs 42, 9%; p<0, 001) and stroke (1, 8% vs 12, 7%; p=0, 023). They also had lower values of CHA2DS2-VASc (2, 23 vs 3, 19; p<0, 001) and HAS-BLED scores (0, 6 vs 1, 03; p=0, 005) scores and were more treated with direct oral anticoagulants (77, 8% vs 54, 5%; p=0, 01) than vitamin K antagonists. 64, 6% remained in sinus rhythm one year after EC (vs 42, 6%; p=0, 026). During a median follow-up of 1338 days, no significant differences were found regarding all-cause mortality, but we report a lower rate of CV death in AIC patients (3, 8% vs 25, 5%; p=0, 002). Conclusion: In our study, 46, 3% of patients with reduced LVEF had AIC, which was associated with a significantly lower rate of CV death. Given the prognostic impact of this diagnosis, EC should be considered as a primary strategy in patients with high suspicion of AIC due to AF/AFL.